Pengembangan Bahan Ajar Matematika Berbasis Google Sites Untuk Memecahkan Masalah Matematis Pada Siswa Kelas VI SDS IT Al Fauzi - Mhd Arif Setiawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to produce mathematics teaching materials based on google sites to solve mathematical problems in grade VI students of SDS IT Al Fauzi, with valid, practical and effective levels in learning. This study is a development research with the ADDIE model, in which the phases are: analysis, planning, development, implementation, and evaluation stages. The study instruments used were validity sheets, practicality, student assessment and problem solving tests. The validity results show that the resulting product gets a very good achievement, with the level of problem solving test getting 87% achievement and entering a very good achievement. Thus, the conclusion is that the product developed, namely math teaching materials based on google sites to solve mathematical problems in grade VI students of SDS IT Al Fauzi, has a valid, practical and effective quality in its use in class when learning.